Hematopoietic Pyk2 regulates migration of differentiated HL-60 cells - Duan Yingli; Learoyd Jonathan; Wang Lin; Leff Alan R; Zhu Xiangdong (BMC, 2010)
Abstract Background Pyk2 is a non-receptor cytoplasmic tyrosine kinase that belongs to the focal adhesion kinase family and has been implicated in neutrophil spreading and respiratory burst activity caused by TNF-α. However, the role of Pyk2 in neutrophil migration is incompletely defined. In this study, we tested the hypothesis that Pyk2 regulates the migration of neutrophil-like differentiated HL-60 cells subsequent to β2-integrin mediated cell adhesion. Methods HL-60 cells were induced to differentiate into neutrophil-like cells (dHL60) by incubation in medium containing 1.25% DMSO for up to 4 days. Pyk2 expression and tyrosine phosphorylation was measured by Western blot analysis. Adhesion of dHL60 cells to plated fibrinogen was measured by residual myeloperoxidase activity. dHL60 cell migration was evaluated using a 96-well chemoTx chamber. Results Western blot analysis demonstrated that hematopoietic Pyk2 was predominantly expressed after HL60 cell differentiation. Pyk2 was tyrosine phosphorylated upon adhesion of dHL60 cells to plated fibrinogen in the presence of fMLP. By contrast, tyrosine phosphorylation of Pyk2 was insignificant in dHL60 cells treated in suspension with fMLP. Antibodies against CD18 blocked both phosphorylation of Pyk2 and adhesion of dHL60 cells to fibrinogen, demonstrating that phosphorylation of Pyk2 was β2-integrin dependent. TAT-Pyk2-CT, a dominant negative fusion protein in which the TAT protein transduction domain was fused to the c-terminal Pyk2, attenuated fMLP-stimulated spreading, migration and phosphorylation of endogenous Pyk2 without blocking adhesion of dHL-60 cells to fibrinogen. Similarly, silencing of Pyk2 expression by siRNA in dHL60 cells also attenuated dHL60 cell migration caused by fMLP. Phospho-Pyk2 was evenly distributed around cell membrane circumferentially in unstimulated dHL-60 cells adherent to plated fibrinogen. In dHL60 cells treated with fMLP to cause cell spreading and polarization, Pyk2 was concentrated at the leading edge of pseudopods or at the trailing edge of uropods during migration of neutrophilic dHL-60 cells. Conclusions We conclude that Pyk2 is activated by β2-integrin adhesion. The activated concentration of Pyk2 and colocalization with F-actin in pseudopodia suggests that Pyk2 may regulate cell spreading and migration in dHL60 cells.